El liderazgo en una perspectiva internacional: un estudio comparativo entre líderes brasileños y españoles de acuerdo con el proyecto globe - Barata, Meirijane Anastácio (2011)
The main objective of the present study is to analyse organizational leaders’ styles in Spain and Brazil. The proposed comparative study among Spanish and Brazilian organizational leaders follows the GLOBE (Global Leadership and Organizational Behaviour Effectiveness) project according to its methods and goals. For the present research 40 Spanish and 40 Brazilian enterprises were approached in a transversal and correlation study with the participation of 83 Spanish and 88 Brazilian organizational leaders. Both directors (20%) and managers (80%) took part in the study. Comparatively, the main results point to differences among Brazilian and Spanish leaders in what concerns the following leadership dimensions: authoritarianism, relationship and anticipation for changing. On the other hand, it was found a negative relationship between authoritarianism and social ability;; a positive relationship between authoritarianism and relation, as well as a positive relation between relationships and social ability. At last it was discussed the limitations and practical implications of the found results for leadership in organizations of both approached countries, comparatively.